2008
DOI: 10.2143/ac.63.6.2033395
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in risk factors and outcomes after cardiac rehabilitation

Abstract: Following a short-term cardiac rehabilitation programme, modification in cardiac risk factors and quality of life occurs. Both genders benefit alike in most aspects from this programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Studies have shown that women are less likely to be referred to and enroll in CR 25 despite having more co-morbid conditions than men. 26 Our results further highlight the need for programs to target increased participation for women as they experience similar improvement in CR as men. 26 …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Studies have shown that women are less likely to be referred to and enroll in CR 25 despite having more co-morbid conditions than men. 26 Our results further highlight the need for programs to target increased participation for women as they experience similar improvement in CR as men. 26 …”
Section: Discussionmentioning
confidence: 56%
“…26 Our results further highlight the need for programs to target increased participation for women as they experience similar improvement in CR as men. 26 …”
Section: Discussionmentioning
confidence: 56%
“…Of the 103 middle-income countries globally, this search revealed CR services exist in 29 (28.2%) countries (Figure 1). These were: Algeria, 70 Argentina,42 Belarus, 69 Bosnia And Herzegovina, 69 Brazil, 68 Bulgaria, 69 China, 71 Colombia, 68 Costa Rica, 69 Cuba, 69 Ecuador, 42 Egypt, 72 India, 73 Indonesia, 74 Iran, 75 Malaysia, 69 Mexico, 68 Pakistan, 76 Panama, 69 Paraguay, 42 Peru, 68 Philippines, 43 Romania, 77 South Africa, 78 Sri Lanka, 69 Thailand, 69 Tunisia, 79 Turkey, 80 and Venzuela. 42 …”
Section: Cr Availability In Middle-income Countriesmentioning
confidence: 99%
“…In middle-income countries, women are similarly less represented than men (<30%) in CR. 73,75,100,101 Indeed in one CR study in Brazil, there were no women represented. 102 Given there is no evidence that these vulnerable groups derive less clinical benefit from CR, these disparities suggest that some vulnerable groups have even less access to CR than does the average patient.…”
Section: Disparities In Patient Access To Crmentioning
confidence: 99%
“…It is well-established that CR results in significant reductions in CV mortality and morbidity, among other benefits also demonstrated in the EMR [6,7]. Despite this and its costeffectiveness [6,8,9], CR is not readily available in the region.…”
Section: Introductionmentioning
confidence: 99%